2015
DOI: 10.1038/gt.2015.59
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-targeted microbubble destruction-mediated microRNA-21 transfection regulated PDCD4/NF-κB/TNF-α pathway to prevent coronary microembolization-induced cardiac dysfunction

Abstract: The programmed cell death 4/nuclear factor-κB/tumor necrosis factor α (PDCD4/NF-κB/TNF-α) signaling pathway has an important role in coronary microembolization (CME)-induced inflammation. microRNA-21 protects myocardium mainly via regulation of its target gene PDCD4. Therefore, in this study we investigated the effect of ultrasound-guided microbubble-mediated microRNA-21 transfection on cardiac function in CME pig model and determined the potential mechanisms involved. The pig CME model was established by micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…This result was consistent with Liang's report, which showed that downregulated PDCD4 suppressed the expression of proinflammatory factors and promoted the production the anti-inflammatory factor, IL-10 [24]. Other studies suggest that the PDCD4/nuclear factor- κ B/tumor necrosis factor α (PDCD4/NF- κ B/TNF- α ) signaling pathway plays an important role in coronary microembolization- (CME-) induced inflammation, and inhibition of PDCD4 could improve CME-induced cardiac dysfunction [41]. Moreover, PDCD4 improved the inflammatory response via nuclear factor- κ B (NF- κ B), activating and inhibiting the production of IL-10 [24].…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with Liang's report, which showed that downregulated PDCD4 suppressed the expression of proinflammatory factors and promoted the production the anti-inflammatory factor, IL-10 [24]. Other studies suggest that the PDCD4/nuclear factor- κ B/tumor necrosis factor α (PDCD4/NF- κ B/TNF- α ) signaling pathway plays an important role in coronary microembolization- (CME-) induced inflammation, and inhibition of PDCD4 could improve CME-induced cardiac dysfunction [41]. Moreover, PDCD4 improved the inflammatory response via nuclear factor- κ B (NF- κ B), activating and inhibiting the production of IL-10 [24].…”
Section: Discussionmentioning
confidence: 99%
“…CME may also result in myocardial contractile dysfunction and notable arrhythmias which are strongly associated with cardiac dysfunction and deterioration of clinical follow-ups [5-7]. Recently, research has found that microRNAs (miRs) and myocardial autophagy may play a vital role in CME [8, 9]; however, the specific molecular mechanism of these factors remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Among the differentially expressed miRNAs, miR-21 showed the most significant increase in expression, and it played a protective role in hypoxia/ reoxygenation-induced apoptosis by regulating the expression of programmed cell death factor 4 [14]. Our previous study also found that overexpression of miR-21 inhibited CME-induced myocardial inflammatory response and improved heart function via inhibition of the PDCD4/NF-κB/TNF-α signaling pathway [15]. Still, the expression and mechanism of action of other miRNAs involved in CME-induced myocardial injury need to be elucidated.…”
Section: Introductionmentioning
confidence: 99%